2015
DOI: 10.1007/s40011-015-0585-y
|View full text |Cite
|
Sign up to set email alerts
|

Microglia in the Physiology and Pathology of Brain

Abstract: Microglia are the immune cells of the brain involved in regulation and maintenance of brain microenvironment. These cells not only play imperative role in shaping the brain neural networks during development but also protect the brain from any disparaging condition throughout the life as first line of combatants. Interestingly, these cells exhibit dual nature in various neuropathological conditions. Depending upon the quantum of brain insult, they acquire different morphology which in favour either suppress th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 167 publications
(186 reference statements)
0
2
0
Order By: Relevance
“…Using these newly generated mouse lines, we found that 5xFAD Inpp5d ΔMG mice had more microglia in the cortex and dentate gyrus of the hippocampus as measured by the number of IBA1+ microglia and the total IBA1+ volume at 5 months of age (Figure 1A‐C, Figure S1A‐C). Microglia activation is often accompanied by a shift toward a larger and more amoeboid morphology 3,34 . By measuring IBA1+ volume per microglia, we found that SHIP‐1 deficient microglia in both the cortex and dentate gyrus were ∼2.5‐fold larger in size and qualitatively displayed a more amoeboid morphology compared to microglia from 5xFAD littermate control mice (Figure 1D, Figure S1D), suggesting enhanced activation.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Using these newly generated mouse lines, we found that 5xFAD Inpp5d ΔMG mice had more microglia in the cortex and dentate gyrus of the hippocampus as measured by the number of IBA1+ microglia and the total IBA1+ volume at 5 months of age (Figure 1A‐C, Figure S1A‐C). Microglia activation is often accompanied by a shift toward a larger and more amoeboid morphology 3,34 . By measuring IBA1+ volume per microglia, we found that SHIP‐1 deficient microglia in both the cortex and dentate gyrus were ∼2.5‐fold larger in size and qualitatively displayed a more amoeboid morphology compared to microglia from 5xFAD littermate control mice (Figure 1D, Figure S1D), suggesting enhanced activation.…”
Section: Resultsmentioning
confidence: 91%
“…Microglia activation is often accompanied by a shift toward a larger and more amoeboid morphology. 3,34 By measuring IBA1+ volume per microglia, we found that SHIP-1 deficient microglia in both the cortex and dentate gyrus were ∼2.5-fold larger in size and qualitatively displayed a more amoeboid morphology compared to microglia from 5xFAD littermate control mice (Figure 1D, Figure S1D), suggesting enhanced activation. To determine if loss of SHIP-1 influences microglia physiology in the absence of Aβ pathology, we next assessed microglial numbers and morphology in the cortex of Inpp5d ΔMG mice that do not express the 5xFAD transgenes (further referred to as wildtype [WT] Inpp5d ΔMG mice) and Inpp5d fl/fl littermate controls (further referred to as WT mice).…”
Section: Ship-1 Deletion Increases Microglial Numbers and Mobilizatio...mentioning
confidence: 98%